Extracellular alkaline phosphatase from the filamentous fungus Aspergillus caespitosus: Purification and biochemical characterization - GUIMARAES, L. H. S; TERENZI, H. F; JORGE, J. A; LEONE, F. A; POLIZELI, M. L. T. M (Folia microbiologica, 2003)
Among 30 species of filamentous fungi isolated from Brazilian soil, Aspergillus caespitosus produced and secreted the highest levels of alkaline phosphatase in culture medium supplemented with xylan. The extracellular alkaline phosphatase was purified by DEAE-cellulose and concanavalin A-sepharose chromatography. The enzyme was a glycoprotein containing up to 56% sugar with molar mass of 134.8 kDa, according to gel filtration in Sepharose CL-6B, and 57 kDa according to SDS-PAGE. Nondenaturing electrophoresis (6% PAGE) of the purified enzyme produced a single band, suggesting that the native enzyme was a homodimer. Optima of temperature and pH were 75 degrees C and 8.5, respectively. The enzyme was stable at 50 degrees C and its activity was enhanced by 95% in the presence of Mg2+ (1 mmol/L). 4-Nitrophenyl phosphate was the preferentially hydrolyzed substrate with K(m) and upsilon lim values of 74 mumol/L and 285 mumol/s, in the absence, and 90 mumol/L and 418 mumol/s, in the presence of Mg2+, respectively. The enzyme also hydrolyzed other phosphorylated amino acids (O-phosphothreonine, O-phosphotyrosine, O-phosphoserine).